The Influence of Live Streamer Interaction on Purchase Intention with Brand Love as a Moderating Variable - Anshar Daud; Syarifuddin; Erry Donneli; Wahid; Rudy Irwansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Researchers also believe that Live Streaming-Interaction on TikTok can increase purchasing decisions because more and more people know about brand types, brand quality, brand suitability, brand identity, and so on. Therefore, this research aims to analyze the influence of Live-Streamer Interaction on Purchasing Decisions. Different from previous research, this research adds the Brand Love variable as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research was obtained from distributing online questionnaires to 350 TikTok shop sellers and buyers on certain dates. These data can be called primary data. These data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Live-Streaming Interaction variable can have a positive relationship and a significant influence on purchasing decisions because the P-Values value is positive and is below the significance level of 0.05, namely 0.004. Otherwise, the Brand Love variable can moderate the influence of the Live-Streamer Interaction variable on the Purchase Decision variable because the P-Values results show a positive direction and are below 0.05. Thus the first and second hypotheses in this research can be proven and accepted.